The Moderating Role of Green Tax on the Relationship Between ESG Performance and Environmental Pollution - Hossein Fakhari,; Amir Mohammad Askari,; Hani Shirowzhan,; Khadijeh Namvar Vansofla,; Amirmohammad Esmaeilpour Eshka, (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: Environmental, social, and governance (ESG) compliance can enhance business performance and contribute to sustainable development by reducing pollutants; however, this assertion lacks substantial evidence in practice. Therefore, this study investigates how ESG performance affects environmental pollutants and the role of the Green Tax law in moderating this relationship. The primary contribution of this research is to analyse the impact of ESG performance on pollutants and investigate the moderating effect of the Green Tax law. The study specifically examines whether the assertion of compliance with ESG requirements reduces pollution or if it instead facilitates greenwashing, thereby masking the true environmental impact.. Design/Methodology/Approach: Using multiple regression and panel data analysis, data from 91 companies listed on the Tehran Stock Exchange (TSE) between 2020 and 2022 were analyzed. Research findings: Higher ESG performance is associated with increased pollution, and the Green Tax law significantly amplifies this effect. Theoretical contribution/Originality: The findings suggest that ESG performance is linked to increased pollution, indicating potential for greenwashing. ESG reporting legitimises businesses and reduces litigation risk, with companies exploiting gaps in the law to maintain pollution levels. Practitioner/Policy implication: The study highlights greenwashing in publicly listed companies. Recommendations include implementing climate policies, promoting renewable energy sources, increasing employee awareness, encouraging whistleblowing, implementing green taxes, and training inspectors and other stakeholders. Research Limitations: The findings are limited by the short threeyear study period and the restricted sample of TSE-listed firms, which constrain the generalisability of the results across broader contexts and longer time horizons. Future studies incorporating extended time frames, additional industries, and more comprehensive environmental reporting would provide deeper insight into long-term ESG dynamics and greenwashing behaviour.